Institutional trauma across the Americas: Covid-19 as slow crisis. (July 2022) - Robinson, Laura
Building on theories of cultural trauma, this research examines institutional trauma engendered by the pandemic in relation to journalism and public health in the US and Brazil. The trauma stemming from Covid-19 marks a transformational crisis not only in terms of global public health but also collective confidence in institutions writ large. To probe these issues, this article takes advantage of a vibrant digital discussion among Americans and Brazilians hosted by three flagship newspapers in the two countries: The New York Times, Folha de S. Paulo, and O Estado de S. Paulo. The analysis reveals that both groups experience Covid-accelerated trauma that undermines Brazilians' and Americans' faith in foundational institutions' ability to adequately respond to the pandemic. Comparing these interpretations of the Covid-19 crisis in the US and Brazil allows us to see how the acute health crisis triggered by the virus morphs into a form of institutional trauma, with deep implications for collective confidence in public health, journalism, and democracy.